Wood-like plate with colored flow lines and manufacturing method of wood-like plate
A multi-layered wood-like board with colored flow patterns addresses the aesthetic limitations of traditional wood-plastic composites by incorporating an aging-resistant surface layer, a primary grooved pattern board, and a wear-resistant bottom layer, achieving vibrant and textured surfaces suitable for diverse applications.
Patent Information
- Application Number
- CN202411224203.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-20
AI Technical Summary
Traditional wood-plastic composite materials lack vibrant surface aesthetics and color variety, making them unsuitable for replacing high-end solid wood products.
A multi-layered wood-like board with colored flow patterns is created by combining an aging-resistant color flow pattern surface layer, a primary color flow pattern plastic wood board with grooved patterns, and a wear-resistant color flow pattern bottom layer, using specific materials and processing techniques to achieve rich surface colors and textures.
The solution results in a wood-like board with enhanced surface aesthetics and color variety, ensuring the integrity of the board's structure and texture, while meeting various usage needs through controlled layer thickness and color combinations.
Smart Images

Figure HSA0000299688690000011 
Figure HSA0000299688690000012
Abstract
Description
Technical Field
[0001] The invention relates to a composite material board, in particular to a wood-like board with colored flow patterns and a preparation method thereof, belonging to the technical field of ecological environment materials and composite materials. Background Art
[0002] Wood-plastic composite materials are a new type of chemical material that has developed rapidly in recent years. They are made of waste plastics and agricultural and forestry scraps such as wood powder and rice bran as the main raw materials, and then a small amount of additives are added and extruded at high temperature. It combines the main advantages of thermoplastic polymers and wood, and has the advantages of anti-corrosion, moisture-proof, insect-proof, high dimensional stability, no cracking, no warping, and no toxic components. It has been widely used as outdoor flooring, swimming pool edging, flower boxes, tree pools, fences, trash cans, sun visors, benches, chair strips, backrest strips, leisure tables, signs, bulletin boards, beams, dock planks, water channels, handrails, guardrails, fences, partitions, flower rack corridors, outdoor pavilions, open-air platforms, bathroom panels, door and window frame covers, sound-absorbing panels, roof panels, etc. However, traditional wood-plastic composite materials are generally made by directly melting and mixing plastics such as polyethylene and polypropylene with wood powder, rice bran, etc. and then extruding them. The resulting wood-plastic materials have a single color, are not bright enough, and have poor surface aesthetics, making it very difficult for wood-plastic composite materials to replace high-end solid wood products.
[0003] Therefore, it is necessary to invent a wood-like board with colored flow patterns, which overcomes the shortcomings of conventional wood-plastic composite materials and has rich surface colors, so that it can replace wood to a greater extent. Summary of the invention
[0004] The present invention is aimed at the above purpose and provides a wood-like board with colored flow patterns and a manufacturing method thereof.
[0005] The utility model discloses a wood-like board with color flow patterns, which is composed of an aging-resistant color flow pattern surface layer, a primary color flow pattern plastic wood board with grooved patterns and a wear-resistant color flow pattern bottom layer from top to bottom.
[0006] The anti-aging color flow pattern surface layer is formed by melt-blending and extruding high-density polyethylene, color masterbatch one, color masterbatch two, antioxidant 1010, nano zinc oxide and stearic acid.
[0007] The wear-resistant color flow pattern bottom layer is formed by melt-blending and extruding high-density polyethylene, masterbatch, modified nano silicon dioxide, graphite powder and stearic acid; the modified nano silicon dioxide is nano silicon dioxide treated with a γ-(methacryloyloxy)propyltrimethoxysilane coupling agent.
[0008] The primary color flow plastic wood board with grooved pattern is formed by combining the main particle material of the board and the masterbatch melt to form a plastic wood multicolor fluid, which is divided into multiple fluids after passing through a diverter cone, extruded to form a primary color flow plastic wood board, and then squeezed into a grooved pattern by a pressure roller; the main particle material of the board is formed by melt blending and extrusion granulation of high-density polyethylene, modified wood powder, heavy calcium carbonate powder, chlorinated polyethylene and calcium stearate; the modified wood powder is formed by atomizing and spraying oleic acid-based dye liquid on the primary modified wood powder; the primary modified wood powder is prepared by treating wood powder with calcium chloride aqueous solution and sodium carbonate aqueous solution; the oleic acid-based dye liquid is prepared by mixing dye and oleic acid; the grooved pattern is composed of grooved main stripes, grooved wing stripes and grooved branch stripes.
[0009] A wood-like board with colored flow patterns, the manufacturing method of which comprises the following steps:
[0010] (1) Weighing wood powder, calcium chloride, sodium carbonate, oleic acid and dye according to a mass ratio of 100:3-11:3-11:1-5:0.3-0.7, respectively preparing calcium chloride and sodium carbonate into calcium chloride aqueous solution and sodium carbonate aqueous solution, respectively, immersing the wood powder completely in the calcium chloride aqueous solution and stirring evenly, then adding the sodium carbonate aqueous solution, stirring evenly again, stopping stirring after 30-60 minutes, filtering to remove water, and drying to obtain primary modified wood powder; mixing the dye and oleic acid evenly to form an oleic acid-based dye liquid; using an atomization spraying technology to mix the oleic acid-based dye liquid and the primary modified wood powder evenly, and heating to 60-80°C, keeping the temperature for 30-60 minutes, then cooling to room temperature, and sieving to obtain modified wood powder; the dye is a linoleic acid dye or a phthalocyanine dye; the modified wood powder has a particle size of 40-160 mesh;
[0011] (2) High-density polyethylene, modified wood flour, heavy calcium carbonate powder, chlorinated polyethylene and calcium stearate are weighed respectively according to a mass ratio of 100:100-300:10-30:3-7:2-6, mixed evenly and added into a granulator, melt-blended at 170-190° C., extruded and granulated to obtain a main granular material of the board; the particle size of the heavy calcium carbonate powder is 200-1100 mesh;
[0012] (3) Select a single-screw extruder, set a side feed port between the extruder head and the main feed port, the center line of the side feed port is 1-2 meters away from the center line of the main feed port, and form an angle of 20-30° with the main feed port, and install a splitter cone at the confluence core between the extrusion screw and the die;
[0013] (4) Add the main pellets of the board into the extruder through the main feeding port, heat and melt, the screw temperature is 165-185°C, the screw speed is 20-30r / min, and the masterbatch is added from the side feeding port at the same time, and the mass ratio of the masterbatch added per unit time to the main pellets of the board is controlled to be 0.3-1.9:100. The masterbatch melts after entering the extruder and combines with the melt of the main pellets of the board to form a plastic wood multi-color fluid, which is divided into multiple streams after passing through the diverter cone, and extruded through the die to form a primary color flow pattern plastic wood board with color flow patterns on the surface;
[0014] (5) When the surface temperature of the primary color flow plastic wood board drops to 60-100°C, a groove pattern is pressed on the surface of the primary color flow plastic wood board by using a roller extrusion technology. The groove pattern consists of a groove main stripe, a groove wing stripe and a groove branch stripe. The distance between two adjacent groove main stripes is 12-20 cm. The length of each groove main stripe is 20-30 cm, and the width is 1-3 cm. The depth of the groove main stripe gradually becomes shallower from the head to the tail, wherein the depth of the groove main stripe head is 0.7-1.1 mm, and the depth of the groove main stripe tail is 0.3-0.5 mm; each groove main stripe is distributed on both sides with 2-4 groove wing stripes, each groove main stripe has a groove wing stripe, and each groove main stripe has a groove wing stripe. The grooved wing stripes form an angle of 10-70° with the grooved main stripes, the length of the grooved wing stripes is 3-5cm, the width is 0.8-1.2cm, the depth of the grooved wing stripes gradually becomes shallower from the head to the tail, and the depth of the tail of the grooved wing stripes is 0.2-0.6 times the depth of the head of the grooved wing stripes; there are 1-5 grooved branch stripes on both sides of each grooved wing stripe, the length of each grooved branch stripe is 5-11mm, the width is 1-3mm, the depth of the grooved branch stripes gradually becomes shallower from the head to the tail, and the depth of the tail of the grooved branch stripes is 0.1-0.3 times the depth of the head of the grooved branch stripes, forming a primary color flow pattern plastic wood board with grooved patterns;
[0015] (6) weighing nano-silica and γ-(methacryloxy)propyltrimethoxysilane coupling agent in a mass ratio of 100:1-5, adding γ-(methacryloxy)propyltrimethoxysilane coupling agent into water to prepare a coupling agent solution, then adding nano-silica thereto, dispersing evenly, treating for 10-20 minutes, filtering, drying, and dispersing to obtain modified nano-silica; the modified nano-silica has a particle size of 20-100 nm;
[0016] (7) High-density polyethylene, masterbatch 1, masterbatch 2, antioxidant 1010, nano zinc oxide and stearic acid are weighed respectively according to a mass ratio of 100:1-5:1-5:0.4-0.8:0.4-0.8:0.6-1.2, mixed evenly and added into a granulator, melt blended at 170-190° C., extruded and granulated to obtain aging-resistant colored plastic particles; the particle size of the nano zinc oxide is 20-60 nm; the melt index of the masterbatch 1 and the masterbatch 2 differs by 0.6-6 g / 10 min (2.16 kgf, 190° C.);
[0017] (8) High-density polyethylene, masterbatch, modified nano-silicon dioxide, graphite powder and stearic acid are weighed respectively according to a mass ratio of 100:1-5:0.6-1.2:0.1-0.3:0.8-1.6, mixed evenly and added into a granulator, melt-blended at 170-190° C., extruded and granulated to obtain wear-resistant colored plastic particles;
[0018] (9) Adding aging-resistant colored plastic particles and wear-resistant colored plastic particles into two extruders respectively, the processing temperature of extruder one is 160-190° C., and the processing temperature of extruder two is 160-190° C., to form aging-resistant colored plastic molten material flow and wear-resistant colored plastic molten material flow, which are respectively coated on the upper and lower surfaces of the primary colored flow pattern plastic wood board with grooved pattern after being extruded through respective dies to form primary colored flow pattern wood-like board materials, which are then roller extruded, cooled and shaped to obtain colored flow pattern wood-like board materials.
[0019] The present invention:
[0020] (1) A multi-layer composite method was used to prepare a wood-like board with colored flow patterns, which has a unique structure and good wood-like effect;
[0021] (2) The primary color flow pattern plastic wood board is made of dyed wood powder, and the color is firm; by processing the groove pattern, the flow pattern effect is ensured, and at the same time, the aging-resistant color flow pattern surface layer is ensured to be firmly combined with the upper surface of the primary color flow pattern plastic wood board with the groove pattern and the wear-resistant color flow pattern bottom layer is ensured to be firmly combined with the lower surface of the primary color flow pattern plastic wood board with the groove pattern, thereby ensuring the integrity of the board and the main texture of the upper and lower surfaces;
[0022] (3) Using masterbatch to make the aging-resistant color flow pattern surface layer and the wear-resistant color flow pattern bottom layer. According to the needs of wood imitation, by selecting masterbatch of different colors, different color effects can be achieved on the upper and lower surfaces;
[0023] (4) Two masterbatches with different melt indexes are used in the aging-resistant color flow pattern surface layer. Different color combinations can be formed by utilizing the difference in fluidity between the two, thereby making the surface color of the plastic wood board more colorful;
[0024] (5) By controlling the extrusion speed of the aging-resistant colored plastic melt flow, the extrusion speed of the wear-resistant colored plastic melt flow and the moving speed of the primary colored flow pattern plastic wood board with grooved pattern, the thickness of the upper and lower surface layers of the board can be controlled to better meet different usage needs;
[0025] (6) Although the present invention provides that the upper and lower surfaces correspond to the aging-resistant color flow pattern surface layer and the wear-resistant color flow pattern bottom layer respectively, and the formulas are different, according to actual use needs, the surface layer and the bottom layer can also be made with the same formula. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention will be further described below in conjunction with the accompanying drawings.
[0027] Figure 1 It is a schematic diagram of the structure of a wood-like board with colored flow patterns.
[0028] Figure 2 yes Figure 1 Schematic diagram of the structure of primary color flow plastic wood board with grooved pattern.
[0029] 1-aging-resistant color flow pattern surface layer, 2-primary color flow pattern plastic wood board with grooved pattern, 3-wear-resistant color flow pattern bottom layer, 4-grooved main stripes, 5-grooved wing stripes, 6-grooved branch stripes, 7-grooved main stripe head, 8-grooved main stripe tail, 9-grooved wing stripe head, 10-grooved wing stripe tail, 11-grooved branch stripe head, 12-grooved branch stripe tail. DETAILED DESCRIPTION
[0030] Refer to the attached Figure 1 A wood-like board with colored flow patterns is composed of an aging-resistant colored flow pattern surface layer 1, a primary colored flow pattern plastic wood board 2 with a grooved pattern, and a wear-resistant colored flow pattern bottom layer 3 from top to bottom.
[0031] The anti-aging color flow pattern surface layer 1 is formed by melt-blending and extruding high-density polyethylene, masterbatch 1, masterbatch 2, antioxidant 1010, nano zinc oxide and stearic acid.
[0032] The wear-resistant color flow pattern bottom layer 3 is formed by melt-blending and extruding high-density polyethylene, masterbatch, modified nano-silicon dioxide, graphite powder and stearic acid; the modified nano-silicon dioxide is nano-silicon dioxide treated with γ-(methacryloyloxy)propyltrimethoxysilane coupling agent.
[0033] The primary colored flow pattern plastic wood board 2 with grooved pattern is formed by combining the main pellets of the board and the masterbatch melt to form a plastic wood multicolor fluid, which is divided into multiple streams after passing through a diverter cone, extruded to form a primary colored flow pattern plastic wood board, and then squeezed into a grooved pattern by a pressure roller; the main pellets of the board are formed by melt blending and extrusion granulation of high-density polyethylene, modified wood powder, heavy calcium carbonate powder, chlorinated polyethylene and calcium stearate; the modified wood powder is formed by atomizing and spraying the primary modified wood powder with oleic acid-based dye liquid; the primary modified wood powder is prepared by treating wood powder with calcium chloride aqueous solution and sodium carbonate aqueous solution; the oleic acid-based dye liquid is prepared by mixing dye and oleic acid; refer to the attached Figure 2 The grooved pattern is composed of a grooved main stripe 4, a grooved wing stripe 5 and a grooved branch stripe 6.
[0034] Embodiment 1: A method for producing a wood-like board with colored flow patterns comprises the following steps:
[0035] (1) Weighing wood powder, calcium chloride, sodium carbonate, oleic acid and linoleic acid dye or phthalocyanine dye according to a mass ratio of 100:7:7:3:0.5, respectively, preparing calcium chloride and sodium carbonate into calcium chloride aqueous solution and sodium carbonate aqueous solution, respectively, immersing the wood powder completely in the calcium chloride aqueous solution and stirring evenly, then adding the sodium carbonate aqueous solution, stirring evenly again, stopping stirring after 45 minutes, filtering to remove water, drying, and obtaining primary modified wood powder; mixing the dye and oleic acid evenly to form an oleic acid-based dye liquid; using an atomization spraying technology to mix the oleic acid-based dye liquid and the primary modified wood powder evenly, and heating to 70°C, keeping the temperature for 45 minutes, then cooling to room temperature, and sieving to obtain a modified wood powder with a particle size of 100 mesh;
[0036] (2) High-density polyethylene, modified wood flour, heavy calcium carbonate powder with a particle size of 650 mesh, chlorinated polyethylene and calcium stearate were weighed respectively in a mass ratio of 100:200:20:5:4, mixed evenly and added into a granulator, melt-blended at 180° C., extruded and granulated to obtain main pellets of the board;
[0037] (3) Select a single-screw extruder, set a side feed port between the extruder head and the main feed port, the center line of the side feed port is 1.5 meters away from the center line of the main feed port, and form an angle of 25° with the main feed port, and install a splitter cone at the confluence core between the extrusion screw and the die;
[0038] (4) The main pellets of the board are added into the extruder through the main feeding port, heated and melted, the screw temperature is 175°C, the screw speed is 25r / min, and the masterbatch is added from the side feeding port at the same time, and the mass ratio of the masterbatch added per unit time to the main pellets of the board is controlled to be 1.1:100. The masterbatch melts after entering the extruder and combines with the melt of the main pellets of the board to form a plastic wood multi-color fluid, which is divided into multiple streams after passing through the diverter cone, and extruded through the die to form a primary color flow pattern plastic wood board with color flow patterns on the surface;
[0039] (5) When the surface temperature of the primary color flow plastic wood board is reduced to 80°C, a groove pattern is pressed on the surface of the primary color flow plastic wood board by using a roller extrusion technology. The groove pattern consists of a groove main stripe 4, a groove wing stripe 5 and a groove branch stripe 6. The distance between two adjacent groove main stripes 4 is 16 cm. The length of each groove main stripe 4 is 25 cm and the width is 2 cm. The depth of the groove main stripe 4 gradually becomes shallower from the head to the tail. The depth of the groove main stripe head 7 is 0.9 mm, and the depth of the groove main stripe tail 8 is 0.4 mm. Each groove main stripe 4 is distributed on both sides with three groove wing stripes 5, each groove main stripe 4 has a groove wing stripe 5. The grooved wing stripe 5 forms an angle of 40° with the grooved main stripe 4. The length of the grooved wing stripe 5 is 4 cm and the width is 1 cm. The depth of the grooved wing stripe 5 gradually becomes shallower from the head to the tail. The depth of the tail 10 of the grooved wing stripe is 0.4 times the depth of the head 9 of the grooved wing stripe. Three grooved branch stripes 6 are distributed on both sides of each grooved wing stripe 5. The length of each grooved branch stripe 6 is 8 mm and the width is 2 mm. The depth of the grooved branch stripe 6 gradually becomes shallower from the head to the tail. The depth of the tail 12 of the grooved branch stripe is 0.2 times the depth of the head 11 of the grooved branch stripe, forming a primary color flow pattern plastic wood board 2 with a grooved pattern;
[0040] (6) weighing nano-silica and γ-(methacryloxy)propyltrimethoxysilane coupling agent in a mass ratio of 100:3, adding γ-(methacryloxy)propyltrimethoxysilane coupling agent to water to prepare a coupling agent solution, and then adding nano-silica thereto, dispersing evenly, treating for 15 minutes, filtering, drying, and dispersing to obtain modified nano-silica with a particle size of 60 nm;
[0041] (7) High-density polyethylene, masterbatch 1, masterbatch 2, antioxidant 1010, nano zinc oxide with a particle size of 40 nm and stearic acid were weighed in a mass ratio of 100:3:3:0.6:0.6:0.9, mixed evenly and added into a granulator, melt-blended at 180° C., extruded and granulated to obtain aging-resistant colored plastic particles; the melt index of the masterbatch 1 and the masterbatch 2 differed by 3.3 g / 10 min (2.16 kgf, 190° C.);
[0042] (8) High-density polyethylene, masterbatch, modified nano-silica, graphite powder and stearic acid are weighed respectively according to a mass ratio of 100:3:0.9:0.2:1.2, mixed evenly and added into a granulator, melt-blended at 180° C., extruded and granulated to obtain wear-resistant colored plastic particles;
[0043] (9) Add aging-resistant colored plastic particles and wear-resistant colored plastic particles into two extruders respectively, the processing temperature of extruder 1 is 175° C., and the processing temperature of extruder 2 is 175° C., to form aging-resistant colored plastic molten material flow and wear-resistant colored plastic molten material flow, which are respectively coated on the upper and lower surfaces of the primary colored flow-grained plastic-wood board 2 with grooved patterns after being extruded through respective dies to form primary colored flow-grained wood-like board materials. The primary colored flow-grained wood-like board materials are then roller extruded, cooled and shaped to obtain a colored flow-grained wood-like board material with an aging-resistant colored flow-grained surface layer 1 on the upper surface, a primary colored flow-grained plastic-wood board 2 with grooved patterns in the middle, and a wear-resistant colored flow-grained bottom layer 3 on the lower surface.
[0044] Embodiment 2: A method for producing a wood-like board with colored flow patterns comprises the following steps:
[0045] (1) Weighing wood powder, calcium chloride, sodium carbonate, oleic acid and linoleic acid dyes according to a mass ratio of 100:3:3:1:0.3, respectively, preparing calcium chloride and sodium carbonate into calcium chloride aqueous solution and sodium carbonate aqueous solution, respectively, immersing the wood powder completely in the calcium chloride aqueous solution and stirring evenly, then adding the sodium carbonate aqueous solution, stirring evenly again, stopping stirring after 30 minutes, filtering to remove water, drying, and obtaining primary modified wood powder; mixing the dye and oleic acid evenly to form an oleic acid-based dye liquid; using an atomization spraying technology to mix the oleic acid-based dye liquid and the primary modified wood powder evenly, and heating to 60°C, keeping the temperature for 30 minutes, then cooling to room temperature, and sieving to obtain a modified wood powder with a particle size of 40 meshes;
[0046] (2) High-density polyethylene, modified wood flour, heavy calcium carbonate powder with a particle size of 200 mesh, chlorinated polyethylene and calcium stearate were weighed respectively in a mass ratio of 100:100:10:3:2, mixed evenly and added into a granulator, melt-blended at 170° C., extruded and granulated to obtain main pellets of the board;
[0047] (3) Select a single-screw extruder, set a side feed port between the extruder head and the main feed port, the center line of the side feed port is 1 meter away from the center line of the main feed port, and form an angle of 20° with the main feed port, and install a splitter cone at the confluence core between the extrusion screw and the die;
[0048] (4) The main pellets of the board are added into the extruder through the main feeding port, heated and melted, the screw temperature is 165°C, the screw speed is 20r / min, and the masterbatch is added from the side feeding port at the same time, and the mass ratio of the masterbatch added per unit time to the main pellets of the board is controlled to be 0.3:100. The masterbatch melts after entering the extruder and combines with the melt of the main pellets of the board to form a plastic wood multi-color fluid, which is divided into multiple streams after passing through the diverter cone, and extruded through the die to form a primary color flow pattern plastic wood board with color flow patterns on the surface;
[0049] (5) When the surface temperature of the primary color flow plastic wood board drops to 60°C, a groove pattern is pressed on the surface of the primary color flow plastic wood board by using a roller extrusion technology. The groove pattern consists of a groove main stripe 4, a groove wing stripe 5 and a groove branch stripe 6. The distance between two adjacent groove main stripes 4 is 12 cm. The length of each groove main stripe 4 is 20 cm and the width is 1 cm. The depth of the groove main stripe 4 gradually becomes shallower from the head to the tail. The depth of the groove main stripe head 7 is 0.7 mm, and the depth of the groove main stripe tail 8 is 0.3 mm. There are two groove wing stripes 5 on both sides of each groove main stripe 4. The grooved wing stripe 5 forms an angle of 10° with the grooved main stripe 4, the length of the grooved wing stripe 5 is 3 cm, the width is 0.8 cm, the depth of the grooved wing stripe 5 gradually becomes shallower from the head to the tail, and the depth of the grooved wing stripe tail 10 is 0.2 times the depth of the grooved wing stripe head 9; each grooved wing stripe 5 is distributed on both sides with a grooved branch stripe 6, the length of the grooved branch stripe 6 is 5 mm, the width is 1 mm, the depth of the grooved branch stripe 6 gradually becomes shallower from the head to the tail, and the depth of the grooved branch stripe tail 12 is 0.1 times the depth of the grooved branch stripe head 11, forming a primary color flow pattern plastic wood board 2 with a grooved pattern;
[0050] (6) weighing nano-silica and γ-(methacryloxy)propyltrimethoxysilane coupling agent in a mass ratio of 100:1, adding γ-(methacryloxy)propyltrimethoxysilane coupling agent to water to prepare a coupling agent solution, and then adding nano-silica thereto, dispersing evenly, treating for 10 minutes, filtering, drying, and dispersing to obtain modified nano-silica with a particle size of 20 nm;
[0051] (7) According to the mass ratio of 100:1:1:0.4:0.4:0.6, high-density polyethylene, masterbatch 1, masterbatch 2, antioxidant 1010, nano zinc oxide with a particle size of 20 nm and stearic acid were weighed respectively, mixed evenly and added into a granulator, melt-blended at 170° C., extruded and granulated to obtain aging-resistant colored plastic particles; the melt index of the masterbatch 1 and the masterbatch 2 differed by 0.6 g / 10 min (2.16 kgf, 190° C.):
[0052] (8) High-density polyethylene, masterbatch, modified nano-silica, graphite powder and stearic acid are weighed respectively according to a mass ratio of 100:1:0.6:0.1:0.8, mixed evenly and added into a granulator, melt-blended at 170° C., extruded and granulated to obtain wear-resistant colored plastic particles;
[0053] (9) Adding aging-resistant colored plastic particles and wear-resistant colored plastic particles into two extruders respectively, the processing temperature of extruder 1 is 160° C., and the processing temperature of extruder 2 is 160° C., to form aging-resistant colored plastic molten material flow and wear-resistant colored plastic molten material flow, which are respectively coated on the upper and lower surfaces of the primary colored flow-grained plastic-wood board 2 with grooved patterns after being extruded through respective dies to form primary colored flow-grained wood-like board materials. The primary colored flow-grained wood-like board materials are then roller extruded, cooled and shaped to obtain a colored flow-grained wood-like board material with an aging-resistant colored flow-grained surface layer 1 on the upper surface, a primary colored flow-grained plastic-wood board 2 with grooved patterns in the middle, and a wear-resistant colored flow-grained bottom layer 3 on the lower surface.
[0054] Embodiment 3: A method for producing a wood-like board with colored flow patterns comprises the following steps:
[0055] (1) Weighing wood powder, calcium chloride, sodium carbonate, oleic acid and phthalocyanine dye in a mass ratio of 100:11:11:5:0.7, respectively, preparing calcium chloride and sodium carbonate into calcium chloride aqueous solution and sodium carbonate aqueous solution, respectively, immersing the wood powder completely in the calcium chloride aqueous solution and stirring evenly, then adding the sodium carbonate aqueous solution, stirring evenly again, stopping stirring after 60 minutes, filtering to remove water, drying, and obtaining primary modified wood powder; mixing the dye and oleic acid evenly to form an oleic acid-based dye liquid; using an atomization spraying technology to mix the oleic acid-based dye liquid and the primary modified wood powder evenly, heating to 80°C, keeping the temperature for 60 minutes, then cooling to room temperature, sieving, and obtaining a modified wood powder with a particle size of 160 meshes;
[0056] (2) High-density polyethylene, modified wood flour, heavy calcium carbonate powder with a particle size of 1100 mesh, chlorinated polyethylene and calcium stearate were weighed respectively in a mass ratio of 100:300:30:7:6, mixed evenly and added into a granulator, melt-blended at 190° C., extruded and granulated to obtain main pellets of the board;
[0057] (3) Select a single-screw extruder, set a side feed port between the extruder head and the main feed port, the center line of the side feed port is 2 meters away from the center line of the main feed port, and form an angle of 30° with the main feed port, and install a splitter cone at the confluence core between the extrusion screw and the die;
[0058] (4) The main pellets of the board are added into the extruder through the main feeding port, heated and melted, the screw temperature is 185°C, the screw speed is 30r / min, and the masterbatch is added from the side feeding port at the same time, and the mass ratio of the masterbatch added per unit time to the main pellets of the board is controlled to be 1.9:100. The masterbatch melts after entering the extruder and combines with the melt of the main pellets of the board to form a plastic wood multi-color fluid, which is divided into multiple streams after passing through the diverter cone, and extruded through the die to form a primary color flow pattern plastic wood board with color flow patterns on the surface;
[0059] (5) When the surface temperature of the primary color flow plastic wood board drops to 100°C, a groove pattern is pressed on the surface of the primary color flow plastic wood board by using a roller extrusion technology. The groove pattern consists of a groove main stripe 4, a groove wing stripe 5 and a groove branch stripe 6. The distance between two adjacent groove main stripes 4 is 20 cm. The length of each groove main stripe 4 is 30 cm and the width is 3 cm. The depth of the groove main stripe 4 gradually becomes shallower from the head to the tail. The depth of the groove main stripe head 7 is 1.1 mm, and the depth of the groove main stripe tail 8 is 0.5 mm. Each groove main stripe 4 is distributed with four groove wing stripes 5 on both sides. The grooved wing stripe 5 forms an angle of 70° with the grooved main stripe 4. The grooved wing stripe 5 has a length of 5 cm and a width of 1.2 cm. The depth of the grooved wing stripe 5 gradually becomes shallower from the head to the tail. The depth of the tail 10 of the grooved wing stripe is 0.6 times the depth of the head 9 of the grooved wing stripe. Five grooved branch stripes 6 are distributed on both sides of each grooved wing stripe 5. The length of each grooved branch stripe 6 is 11 mm and the width is 3 mm. The depth of the grooved branch stripe 6 gradually becomes shallower from the head to the tail. The depth of the tail 12 of the grooved branch stripe is 0.3 times the depth of the head 11 of the grooved branch stripe, forming a primary color flow pattern plastic wood board 2 with a grooved pattern;
[0060] (6) weighing nano-silica and γ-(methacryloxy)propyltrimethoxysilane coupling agent in a mass ratio of 100:5, adding γ-(methacryloxy)propyltrimethoxysilane coupling agent into water to prepare a coupling agent solution, and then adding nano-silica thereto and dispersing evenly. After treating for 20 minutes, filtering, drying, and dispersing to obtain modified nano-silica with a particle size of 100 nm;
[0061] (7) High-density polyethylene, masterbatch 1, masterbatch 2, antioxidant 1010, nano zinc oxide with a particle size of 60 nm and stearic acid were weighed according to a mass ratio of 100:5:5:0.8:0.8:1.2, mixed evenly and added into a granulator, melt-blended at 190° C., extruded and granulated to obtain aging-resistant colored plastic particles; the melt index of the masterbatch 1 and the masterbatch 2 differed by 6 g / 10 min (2.16 kgf, 190° C.);
[0062] (8) High-density polyethylene, masterbatch, modified nano-silica, graphite powder and stearic acid are weighed respectively according to a mass ratio of 100:5:1.2:0.3:1.6, mixed evenly and added into a granulator, melt-blended at 190° C., extruded and granulated to obtain wear-resistant colored plastic particles;
[0063] (9) Adding aging-resistant colored plastic particles and wear-resistant colored plastic particles into two extruders respectively, the processing temperature of extruder 1 is 190° C., and the processing temperature of extruder 2 is 190° C., to form aging-resistant colored plastic molten material flow and wear-resistant colored plastic molten material flow, which are respectively coated on the upper and lower surfaces of the primary colored flow pattern plastic wood board 2 with grooved patterns after being extruded through respective dies to form primary colored flow pattern imitation wood board materials, which are then roller extruded, cooled and shaped to obtain colored flow pattern imitation wood board materials with an aging-resistant colored flow pattern surface layer 1 on the upper surface, a primary colored flow pattern plastic wood board 2 with grooved patterns in the middle, and a wear-resistant colored flow pattern bottom layer 3 on the lower surface.
[0064] Embodiment 4: A method for producing a wood-like board with colored flow patterns comprises the following steps:
[0065] (1) Weighing wood powder, calcium chloride, sodium carbonate, oleic acid and linoleic acid dye or phthalocyanine dye according to a mass ratio of 100:3:7:5:0.3, respectively, preparing calcium chloride and sodium carbonate into calcium chloride aqueous solution and sodium carbonate aqueous solution, respectively, immersing the wood powder completely in the calcium chloride aqueous solution and stirring evenly, then adding the sodium carbonate aqueous solution, stirring evenly again, stopping stirring after 45 minutes, filtering to remove water, drying, and obtaining primary modified wood powder; mixing the dye and oleic acid evenly to form an oleic acid-based dye liquid; using an atomization spraying technology to mix the oleic acid-based dye liquid and the primary modified wood powder evenly, and heating to 80°C, keeping the temperature for 30 minutes, then cooling to room temperature, sieving, and obtaining a modified wood powder with a particle size of 100 mesh;
[0066] (2) High-density polyethylene, modified wood flour, heavy calcium carbonate powder with a particle size of 200 mesh, chlorinated polyethylene and calcium stearate were weighed respectively in a mass ratio of 100:300:10:5:6, mixed evenly and added into a granulator, melt-blended at 180° C., extruded and granulated to obtain main pellets of the board;
[0067] (3) Select a single-screw extruder, set a side feed port between the extruder head and the main feed port, the center line of the side feed port is 2 meters away from the center line of the main feed port, and form an angle of 20° with the main feed port, and install a splitter cone at the confluence core between the extrusion screw and the die;
[0068] (4) The main pellets of the board are added into the extruder through the main feeding port, heated and melted, the screw temperature is 175°C, the screw speed is 30r / min, and the masterbatch is added from the side feeding port at the same time, and the mass ratio of the masterbatch added per unit time to the main pellets of the board is controlled to be 0.3:100. The masterbatch melts after entering the extruder and combines with the melt of the main pellets of the board to form a plastic wood multi-color fluid, which is divided into multiple streams after passing through the diverter cone, and extruded through the die to form a primary color flow pattern plastic wood board with color flow patterns on the surface;
[0069] (5) When the surface temperature of the primary color flow plastic wood board is reduced to 80°C, a groove pattern is pressed on the surface of the primary color flow plastic wood board by using a roller extrusion technology. The groove pattern consists of a groove main stripe 4, a groove wing stripe 5 and a groove branch stripe 6. The distance between two adjacent groove main stripes 4 is 20 cm. The length of each groove main stripe 4 is 20 cm and the width is 2 cm. The depth of the groove main stripe 4 gradually becomes shallower from the head to the tail. The depth of the groove main stripe head 7 is 1.1 mm, and the depth of the groove main stripe tail 8 is 0.3 mm. Each groove main stripe 4 is distributed on both sides with three groove wing stripes 5, each groove main stripe 4 has a groove wing stripe 5. A grooved wing stripe 5 forms an angle of 70° with the grooved main stripe 4, the length of the grooved wing stripe 5 is 3 cm, the width is 1 cm, the depth of the grooved wing stripe 5 gradually becomes shallower from the head to the tail, and the depth of the grooved wing stripe tail 10 is 0.2 times the depth of the grooved wing stripe head 9; a grooved branch stripe 6 is distributed on both sides of each grooved wing stripe 5, the length of the grooved branch stripe 6 is 8 mm, the width is 3 mm, the depth of the grooved branch stripe 6 gradually becomes shallower from the head to the tail, and the depth of the grooved branch stripe tail 12 is 0.1 times the depth of the grooved branch stripe head 11, forming a primary color flow pattern plastic wood board 2 with a grooved pattern;
[0070] (6) weighing nano-silica and γ-(methacryloxy)propyltrimethoxysilane coupling agent in a mass ratio of 100:3, adding γ-(methacryloxy)propyltrimethoxysilane coupling agent into water to prepare a coupling agent solution, and then adding nano-silica thereto, dispersing evenly, treating for 20 minutes, filtering, drying, and dispersing to obtain modified nano-silica with a particle size of 20 nm;
[0071] (7) High-density polyethylene, masterbatch 1, masterbatch 2, antioxidant 1010, nano zinc oxide with a particle size of 20 nm and stearic acid were weighed respectively in a mass ratio of 100:3:5:0.4:0.6:1.2, mixed evenly and added into a granulator, melt-blended at 180° C., extruded and granulated to obtain aging-resistant colored plastic particles; the melt index of the masterbatch 1 and the masterbatch 2 differed by 6 g / 10 min (2.16 kgf, 190° C.);
[0072] (8) High-density polyethylene, masterbatch, modified nano-silica, graphite powder and stearic acid are weighed respectively according to a mass ratio of 100:1:0.9:0.3:0.8, mixed evenly and added into a granulator, melt-blended at 180° C., extruded and granulated to obtain wear-resistant colored plastic particles;
[0073] (9) Adding aging-resistant colored plastic particles and wear-resistant colored plastic particles into two extruders respectively, the processing temperature of extruder 1 is 190° C., and the processing temperature of extruder 2 is 160° C., to form aging-resistant colored plastic molten material flow and wear-resistant colored plastic molten material flow, which are respectively coated on the upper and lower surfaces of the primary colored flow pattern plastic wood board 2 with grooved patterns after being extruded through respective dies to form primary colored flow pattern imitation wood board materials, which are then roller extruded, cooled and shaped to obtain colored flow pattern imitation wood board materials with an aging-resistant colored flow pattern surface layer 1 on the upper surface, a primary colored flow pattern plastic wood board 2 with grooved patterns in the middle, and a wear-resistant colored flow pattern bottom layer 3 on the lower surface.
[0074] Embodiment 5: A method for producing a wood-like board with colored flow patterns comprises the following steps:
[0075] (1) Weighing wood powder, calcium chloride, sodium carbonate, oleic acid and phthalocyanine dye in a mass ratio of 100:7:11:1:0.5, respectively, preparing calcium chloride and sodium carbonate into calcium chloride aqueous solution and sodium carbonate aqueous solution, respectively, immersing the wood powder completely in the calcium chloride aqueous solution and stirring evenly, then adding the sodium carbonate aqueous solution, stirring evenly again, stopping stirring after 60 minutes, filtering to remove water, drying, and obtaining primary modified wood powder; mixing the dye and oleic acid evenly to form an oleic acid-based dye liquid; using an atomization spraying technology to mix the oleic acid-based dye liquid and the primary modified wood powder evenly, and heating to 60°C, keeping the temperature for 45 minutes, then cooling to room temperature, and sieving to obtain a modified wood powder with a particle size of 160 meshes;
[0076] (2) High-density polyethylene, modified wood flour, heavy calcium carbonate powder with a particle size of 650 mesh, chlorinated polyethylene and calcium stearate were weighed respectively in a mass ratio of 100:100:20:7:2, mixed evenly and added into a granulator, melt-blended at 190° C., extruded and granulated to obtain main pellets of the board;
[0077] (3) Select a single-screw extruder, set a side feed port between the extruder head and the main feed port, the center line of the side feed port is 1 meter away from the center line of the main feed port, and form an angle of 25° with the main feed port, and install a splitter cone at the confluence core between the extrusion screw and the die;
[0078] (4) The main pellets of the board are added into the extruder through the main feeding port, heated and melted, the screw temperature is 185°C, the screw speed is 20r / min, and the masterbatch is added from the side feeding port at the same time, and the mass ratio of the masterbatch added per unit time to the main pellets of the board is controlled to be 1.1:100. The masterbatch melts after entering the extruder and combines with the melt of the main pellets of the board to form a plastic wood multi-color fluid, which is divided into multiple streams after passing through the diverter cone, and extruded through the die to form a primary color flow pattern plastic wood board with color flow patterns on the surface;
[0079] (5) When the surface temperature of the primary color flow plastic wood board drops to 100°C, a groove pattern is pressed on the surface of the primary color flow plastic wood board by using a roller extrusion technology. The groove pattern consists of a groove main stripe 4, a groove wing stripe 5 and a groove branch stripe 6. The distance between two adjacent groove main stripes 4 is 12 cm. The length of each groove main stripe 4 is 25 cm and the width is 3 cm. The depth of the groove main stripe 4 gradually becomes shallower from the head to the tail. The depth of the groove main stripe head 7 is 0.7 mm, and the depth of the groove main stripe tail 8 is 0.4 mm. Each groove main stripe 4 is distributed with four groove wing stripes 5 on both sides. The grooved wing stripe 5 forms an angle of 10° with the grooved main stripe 4. The grooved wing stripe 5 has a length of 4 cm and a width of 1.2 cm. The depth of the grooved wing stripe 5 gradually becomes shallower from the head to the tail. The depth of the tail 10 of the grooved wing stripe is 0.2 times the depth of the head 9 of the grooved wing stripe. Three grooved branch stripes 6 are distributed on both sides of each grooved wing stripe 5. The length of each grooved branch stripe 6 is 11 mm and the width is 1 mm. The depth of the grooved branch stripe 6 gradually becomes shallower from the head to the tail. The depth of the tail 12 of the grooved branch stripe is 0.2 times the depth of the head 11 of the grooved branch stripe, forming a primary color flow pattern plastic wood board 2 with a grooved pattern;
[0080] (6) weighing nano-silica and γ-(methacryloxy)propyltrimethoxysilane coupling agent in a mass ratio of 100:5, adding γ-(methacryloxy)propyltrimethoxysilane coupling agent to water to prepare a coupling agent solution, and then adding nano-silica thereto, dispersing evenly, treating for 10 minutes, filtering, drying, and dispersing to obtain modified nano-silica with a particle size of 60 nm;
[0081] (7) High-density polyethylene, masterbatch 1, masterbatch 2, antioxidant 1010, nano zinc oxide with a particle size of 40 nm and stearic acid were weighed in a mass ratio of 100:5:1:0.6:0.8:0.6, mixed evenly and added into a granulator, melt-blended at 190° C., extruded and granulated to obtain aging-resistant colored plastic particles; the melt index of the masterbatch 1 and the masterbatch 2 differed by 0.6 g / 10 min (2.16 kgf, 190° C.);
[0082] (8) High-density polyethylene, masterbatch, modified nano-silica, graphite powder and stearic acid are weighed respectively according to a mass ratio of 100:3:1.2:0.1:1.2, mixed evenly and added into a granulator, melt-blended at 190° C., extruded and granulated to obtain wear-resistant colored plastic particles;
[0083] (9) Adding aging-resistant colored plastic particles and wear-resistant colored plastic particles into two extruders respectively, the processing temperature of extruder 1 is 160° C., and the processing temperature of extruder 2 is 175° C., to form aging-resistant colored plastic molten material flow and wear-resistant colored plastic molten material flow, which are respectively coated on the upper and lower surfaces of the primary colored flow pattern plastic wood board 2 with grooved patterns after being extruded through respective dies to form primary colored flow pattern imitation wood board materials, which are then roller extruded, cooled and shaped to obtain colored flow pattern imitation wood board materials with an aging-resistant colored flow pattern surface layer 1 on the upper surface, a primary colored flow pattern plastic wood board 2 with grooved patterns in the middle, and a wear-resistant colored flow pattern bottom layer 3 on the lower surface.
[0084] Embodiment 6: A method for manufacturing a wood-like board with colored flow patterns comprises the following steps:
[0085] (1) Weighing wood powder, calcium chloride, sodium carbonate, oleic acid and linoleic acid dyes according to a mass ratio of 100:11:3:3:0.7, respectively, preparing calcium chloride and sodium carbonate into calcium chloride aqueous solution and sodium carbonate aqueous solution, respectively, immersing the wood powder completely in the calcium chloride aqueous solution and stirring evenly, then adding the sodium carbonate aqueous solution, stirring evenly again, stopping stirring after 30 minutes, filtering to remove water, drying, and obtaining primary modified wood powder; mixing the dye and oleic acid evenly to form an oleic acid-based dye liquid; using an atomization spraying technology to mix the oleic acid-based dye liquid and the primary modified wood powder evenly, and heating to 70°C, keeping the temperature for 60 minutes, then cooling to room temperature, and sieving to obtain a modified wood powder with a particle size of 40 meshes;
[0086] (2) High-density polyethylene, modified wood flour, heavy calcium carbonate powder with a particle size of 1100 mesh, chlorinated polyethylene and calcium stearate were weighed respectively in a mass ratio of 100:200:30:3:4, mixed evenly and added into a granulator, melt-blended at 170° C., extruded and granulated to obtain main pellets of the board;
[0087] (3) Select a single-screw extruder, set a side feed port between the extruder head and the main feed port, the center line of the side feed port is 1.5 meters away from the center line of the main feed port, and form an angle of 30° with the main feed port, and install a splitter cone at the confluence core between the extrusion screw and the die;
[0088] (4) The main pellets of the board are added into the extruder through the main feeding port, heated and melted, the screw temperature is 165°C, the screw speed is 25r / min, and the masterbatch is added from the side feeding port at the same time, and the mass ratio of the masterbatch added per unit time to the main pellets of the board is controlled to be 1.9:100. The masterbatch melts after entering the extruder and combines with the melt of the main pellets of the board to form a plastic wood multi-color fluid, which is divided into multiple streams after passing through the diverter cone, and extruded through the die to form a primary color flow pattern plastic wood board with color flow patterns on the surface;
[0089] (5) When the surface temperature of the primary color flow plastic wood board drops to 60°C, a groove pattern is pressed on the surface of the primary color flow plastic wood board by using a roller extrusion technology. The groove pattern consists of a groove main stripe 4, a groove wing stripe 5 and a groove branch stripe 6. The distance between two adjacent groove main stripes 4 is 16 cm. The length of each groove main stripe 4 is 30 cm and the width is 1 cm. The depth of the groove main stripe 4 gradually becomes shallower from the head to the tail. The depth of the groove main stripe head 7 is 0.9 mm, and the depth of the groove main stripe tail 8 is 0.5 mm. Two groove wing stripes 5 are distributed on both sides of each groove main stripe 4. Each groove The grooved wing stripe 5 forms an angle of 40° with the grooved main stripe 4. The grooved wing stripe 5 has a length of 5 cm and a width of 0.8 cm. The depth of the grooved wing stripe 5 gradually becomes shallower from the head to the tail. The depth of the tail 10 of the grooved wing stripe is 0.4 times the depth of the head 9 of the grooved wing stripe. Five grooved branch stripes 6 are distributed on both sides of each grooved wing stripe 5. The length of each grooved branch stripe 6 is 5 mm and the width is 2 mm. The depth of the grooved branch stripe 6 gradually becomes shallower from the head to the tail. The depth of the tail 12 of the grooved branch stripe is 0.3 times the depth of the head 11 of the grooved branch stripe, forming a primary color flow pattern plastic wood board 2 with a grooved pattern.
[0090] (6) Weigh nano-silica and γ-(methacryloxy)propyltrimethoxysilane coupling agent in a mass ratio of 100:1, add γ-(methacryloxy)propyltrimethoxysilane coupling agent into water to prepare a coupling agent solution, then add nano-silica thereto and disperse evenly, treat for 15 minutes, filter, dry, and disperse to obtain modified nano-silica with a particle size of 100 nm;
[0091] (7) High-density polyethylene, masterbatch 1, masterbatch 2, antioxidant 1010, nano zinc oxide with a particle size of 60 nm and stearic acid were weighed in a mass ratio of 100:1:3:0.8:0.4:0.9, mixed evenly and added into a granulator, melt blended at 170° C., extruded and granulated to obtain aging-resistant colored plastic particles; the melt index of the masterbatch 1 and the masterbatch 2 differed by 3.3 g / 10 min (2.16 kgf, 190° C.);
[0092] (8) High-density polyethylene, masterbatch, modified nano-silica, graphite powder and stearic acid are weighed respectively according to a mass ratio of 100:5:0.6:0.2:1.6, mixed evenly and added into a granulator, melt-blended at 170° C., extruded and granulated to obtain wear-resistant colored plastic particles;
[0093] (9) Adding aging-resistant colored plastic particles and wear-resistant colored plastic particles into two extruders respectively, the processing temperature of extruder 1 is 175° C., and the processing temperature of extruder 2 is 190° C., to form aging-resistant colored plastic molten material flow and wear-resistant colored plastic molten material flow, which are respectively coated on the upper and lower surfaces of the primary colored flow pattern plastic wood board 2 with grooved patterns after being extruded through respective dies to form primary colored flow pattern imitation wood board materials, which are then roller extruded, cooled and shaped to obtain colored flow pattern imitation wood board materials with an aging-resistant colored flow pattern surface layer 1 on the upper surface, a primary colored flow pattern plastic wood board 2 with grooved patterns in the middle, and a wear-resistant colored flow pattern bottom layer 3 on the lower surface.
[0094] Embodiment 7: A method for manufacturing a wood-like board with colored flow patterns comprises the following steps:
[0095] (1) Weighing wood powder, calcium chloride, sodium carbonate, oleic acid and linoleic acid dyes according to a mass ratio of 100:5:9:2:0.6, respectively, preparing calcium chloride and sodium carbonate into calcium chloride aqueous solution and sodium carbonate aqueous solution, respectively, immersing the wood powder completely in the calcium chloride aqueous solution and stirring evenly, then adding the sodium carbonate aqueous solution, stirring evenly again, stopping stirring after 40 minutes, filtering to remove water, drying, and obtaining primary modified wood powder; mixing the dye and oleic acid evenly to form an oleic acid-based dye liquid; using an atomization spraying technology to mix the oleic acid-based dye liquid and the primary modified wood powder evenly, and heating to 68°C, keeping the temperature for 38 minutes, then cooling to room temperature, sieving, and obtaining a modified wood powder with a particle size of 80 meshes;
[0096] (2) High-density polyethylene, modified wood flour, heavy calcium carbonate powder with a particle size of 800 mesh, chlorinated polyethylene and calcium stearate were weighed respectively in a mass ratio of 100:120:16:6:3, mixed evenly and added into a granulator, melt-blended at 175° C., extruded and granulated to obtain main pellets of the board;
[0097] (3) Select a single-screw extruder, set a side feed port between the extruder head and the main feed port, the center line of the side feed port is 1.2 meters away from the center line of the main feed port, and form an angle of 28° with the main feed port, and install a splitter cone at the confluence core between the extrusion screw and the die;
[0098] (4) The main pellets of the board are added into the extruder through the main feeding port, heated and melted, the screw temperature is 180°C, the screw speed is 28r / min, and the masterbatch is added from the side feeding port at the same time, and the mass ratio of the masterbatch added per unit time to the main pellets of the board is controlled to be 0.9:100. The masterbatch melts after entering the extruder and combines with the melt of the main pellets of the board to form a plastic wood multi-color fluid, which is divided into multiple streams after passing through the diverter cone, and extruded through the die to form a primary color flow pattern plastic wood board with color flow patterns on the surface;
[0099] (5) When the surface temperature of the primary color flow plastic wood board drops to 90°C, a groove pattern is pressed on the surface of the primary color flow plastic wood board by using a roller extrusion technology. The groove pattern consists of a groove main stripe 4, a groove wing stripe 5 and a groove branch stripe 6. The distance between two adjacent groove main stripes 4 is 15 cm. The length of each groove main stripe 4 is 26 cm and the width is 1.3 cm. The depth of the groove main stripe 4 gradually becomes shallower from the head to the tail. The depth of the groove main stripe head 7 is 0.8 mm, and the depth of the groove main stripe tail 8 is 0.35 mm. Each groove main stripe 4 is distributed on both sides with three groove wing stripes 5. Each groove The grooved wing stripe 5 forms an angle of 50° with the grooved main stripe 4, the length of the grooved wing stripe 5 is 3.5 cm, the width is 0.9 cm, the depth of the grooved wing stripe 5 gradually becomes shallower from the head to the tail, and the depth of the grooved wing stripe tail 10 is 0.5 times the depth of the grooved wing stripe head 9; 4 grooved branch stripes 6 are distributed on both sides of each grooved wing stripe 5, each grooved branch stripe 6 is 9 mm long and 1.3 mm wide, the depth of the grooved branch stripe 6 gradually becomes shallower from the head to the tail, and the depth of the grooved branch stripe tail 12 is 0.15 times the depth of the grooved branch stripe head 11, forming a primary color flow pattern plastic wood board 2 with a grooved pattern;
[0100] (6) weighing nano-silica and γ-(methacryloxy)propyltrimethoxysilane coupling agent in a mass ratio of 100:2, adding γ-(methacryloxy)propyltrimethoxysilane coupling agent into water to prepare a coupling agent solution, and then adding nano-silica thereto and dispersing evenly. After treating for 18 minutes, filtering, drying, and dispersing to obtain modified nano-silica with a particle size of 80 nm;
[0101] (7) High-density polyethylene, masterbatch 1, masterbatch 2, antioxidant 1010, nano zinc oxide with a particle size of 50 nm and stearic acid were weighed in a mass ratio of 100:4:4:0.7:0.5:0.8, mixed evenly and added to a granulator, melt-blended at 175° C., extruded and granulated to obtain aging-resistant colored plastic particles; the melt index of the masterbatch 1 and the masterbatch 2 differed by 4 g / 10 min (2.16 kgf, 190° C.);
[0102] (8) High-density polyethylene, masterbatch, modified nano-silica, graphite powder and stearic acid are weighed respectively in a mass ratio of 100:4:0.8:0.13:1.1, mixed evenly and added into a granulator, melt-blended at 178° C., extruded and granulated to obtain wear-resistant colored plastic particles;
[0103] (9) Adding aging-resistant colored plastic particles and wear-resistant colored plastic particles into two extruders respectively, the processing temperature of extruder 1 is 176° C., and the processing temperature of extruder 2 is 167° C., to form aging-resistant colored plastic molten material flow and wear-resistant colored plastic molten material flow, which are respectively coated on the upper and lower surfaces of the primary colored flow pattern plastic wood board 2 with grooved patterns after being extruded through respective dies to form primary colored flow pattern imitation wood board materials, which are then roller extruded, cooled and shaped to obtain colored flow pattern imitation wood board materials with an aging-resistant colored flow pattern surface layer 1 on the upper surface, a primary colored flow pattern plastic wood board 2 with grooved patterns in the middle, and a wear-resistant colored flow pattern bottom layer 3 on the lower surface.
[0104] The effect of Example 1 is demonstrated by experiments below.
[0105] The test board was prepared according to the method of Example 1, wherein light pink polyethylene masterbatch was used to prepare primary colored flow pattern plastic wood board with colored flow pattern on the surface, light pink polyethylene masterbatch and light yellow polyethylene masterbatch were used to prepare aging-resistant colored plastic particles, and light pink polyethylene masterbatch was used to prepare wear-resistant colored plastic particles.
[0106] After testing, a wood-like board with colored flow patterns has bright colored flow patterns with rich colors. The color gradient along the grooved main stripes, grooved wing stripes and grooved branch stripes is due to the change in groove depth. The stripe sense is strong. The static bending strength of the board is 31.21MPa, and the static bending modulus is 1.93GPa. After being placed outdoors in Yixing City, Jiangsu Province for 12 months (maximum temperature 39.8℃, minimum temperature -8.6℃, average temperature 16.8℃), the retention rates of static bending strength and static bending modulus are 93.85% and 96.12% respectively. There is no obvious change in the appearance color of the board, and the flow patterns are clear.
[0107] The test results show that the obtained wood-like board with colored flow patterns has good mechanical properties, obvious colored flow patterns, good aging resistance and high color stability.
[0108] During the test, the following comparative test was conducted: wood powder was directly used instead of modified wood powder to make the main particles of the board. The static bending strength of the obtained board was 20.86 MPa, and the static bending modulus was 1.38 GPa, which were only 66.84% and 71.50% of that in this embodiment. The surface flow pattern color was relatively simple and not rich, indicating that the wood powder modification in this embodiment can effectively improve the mechanical properties of the board and the richness of the color of the flow pattern on the surface of the board.
[0109] During the test, the following comparative test was conducted: one masterbatch was used to replace two masterbatches with different melt indexes to produce aging-resistant colored plastic particles. The aging-resistant colored flow pattern surface of the obtained plate had a relatively single color and was not as colorful as the present embodiment.
[0110] During the test, the following comparative tests were conducted: the surface of the primary color flow pattern plastic wood board had no groove pattern, and the flow pattern of the obtained board was relatively simple without gradient (layering).
Claims
1. The wood-like board with colored flow lines is characterized by From top to bottom, it is composed of an aging-resistant color flow pattern surface layer, a primary color flow pattern plastic wood board with a grooved pattern, and a wear-resistant color flow pattern bottom layer.
2. The wood-like board with colored flow patterns according to claim 1 is characterized in that The anti-aging color flow pattern surface layer is formed by melt-blending and extruding high-density polyethylene, color masterbatch one, color masterbatch two, antioxidant 1010, nano zinc oxide and stearic acid.
3. The wood-like board with colored flow patterns according to claim 2 is characterized in that The wear-resistant color flow pattern bottom layer is formed by melt-blending and extruding high-density polyethylene, masterbatch, modified nano silicon dioxide, graphite powder and stearic acid; the modified nano silicon dioxide is nano silicon dioxide treated with a γ-(methacryloyloxy)propyltrimethoxysilane coupling agent.
4. The wood-like board with colored flow patterns according to claim 2 is characterized in that The primary color flow plastic wood board with grooved pattern is formed by combining the main particle material of the board and the masterbatch melt to form a plastic wood multicolor fluid, which is divided into multiple fluids after passing through a diverter cone, extruded to form a primary color flow plastic wood board, and then squeezed into a grooved pattern by a pressure roller; the main particle material of the board is formed by melt blending and extrusion granulation of high-density polyethylene, modified wood powder, heavy calcium carbonate powder, chlorinated polyethylene and calcium stearate; the modified wood powder is formed by atomizing and spraying oleic acid-based dye liquid on the primary modified wood powder; the primary modified wood powder is prepared by treating wood powder with calcium chloride aqueous solution and sodium carbonate aqueous solution; the oleic acid-based dye liquid is prepared by mixing dye and oleic acid; the grooved pattern is composed of grooved main stripes, grooved wing stripes and grooved branch stripes.
5. The method for preparing the wood-like board with colored flow patterns according to claim 1, characterized in that The preparation method thereof comprises the following steps: (1) Weighing wood powder, calcium chloride, sodium carbonate, oleic acid and dye according to a mass ratio of 100:3-11:3-11:1-5:0.3-0.7, respectively preparing calcium chloride and sodium carbonate into calcium chloride aqueous solution and sodium carbonate aqueous solution, respectively, immersing the wood powder completely in the calcium chloride aqueous solution and stirring evenly, then adding the sodium carbonate aqueous solution, stirring evenly again, stopping stirring after 30-60 minutes, filtering to remove water, and drying to obtain primary modified wood powder; mixing the dye and oleic acid evenly to form an oleic acid-based dye liquid; using an atomization spraying technology to mix the oleic acid-based dye liquid and the primary modified wood powder evenly, and heating to 60-80°C, keeping the temperature for 30-60 minutes, then cooling to room temperature, and sieving to obtain modified wood powder; the dye is a linoleic acid dye or a phthalocyanine dye; the modified wood powder has a particle size of 40-160 mesh; (2) High-density polyethylene, modified wood flour, heavy calcium carbonate powder, chlorinated polyethylene and calcium stearate are weighed respectively according to a mass ratio of 100:100-300:10-30:3-7:2-6, mixed evenly and added into a granulator, melt-blended at 170-190° C., extruded and granulated to obtain a main granular material of the board; the particle size of the heavy calcium carbonate powder is 200-1100 mesh; (3) Select a single-screw extruder, set a side feed port between the extruder head and the main feed port, the center line of the side feed port is 1-2 meters away from the center line of the main feed port, and form an angle of 20-30° with the main feed port, and install a splitter cone at the confluence core between the extrusion screw and the die; (4) Add the main pellets of the board into the extruder through the main feeding port, heat and melt, the screw temperature is 165-185°C, the screw speed is 20-30r / min, and the masterbatch is added from the side feeding port at the same time, and the mass ratio of the masterbatch added per unit time to the main pellets of the board is controlled to be 0.3-1.9:
100. The masterbatch melts after entering the extruder and combines with the melt of the main pellets of the board to form a plastic wood multi-color fluid, which is divided into multiple streams after passing through the diverter cone, and extruded through the die to form a primary color flow pattern plastic wood board with color flow patterns on the surface; (5) When the surface temperature of the primary color flow plastic wood board drops to 60-100°C, a groove pattern is pressed on the surface of the primary color flow plastic wood board by using a roller extrusion technology. The groove pattern consists of a groove main stripe, a groove wing stripe and a groove branch stripe. The distance between two adjacent groove main stripes is 12-20 cm. The length of each groove main stripe is 20-30 cm, and the width is 1-3 cm. The depth of the groove main stripe gradually becomes shallower from the head to the tail, wherein the depth of the groove main stripe head is 0.7-1.1 mm, and the depth of the groove main stripe tail is 0.3-0.5 mm; each groove main stripe is distributed on both sides with 2-4 groove wing stripes, each groove main stripe has a groove wing stripe, and each groove main stripe has a groove wing stripe. The grooved wing stripes form an angle of 10-70° with the grooved main stripes, the length of the grooved wing stripes is 3-5cm, the width is 0.8-1.2cm, the depth of the grooved wing stripes gradually becomes shallower from the head to the tail, and the depth of the tail of the grooved wing stripes is 0.2-0.6 times the depth of the head of the grooved wing stripes; there are 1-5 grooved branch stripes on both sides of each grooved wing stripe, the length of each grooved branch stripe is 5-11mm, the width is 1-3mm, the depth of the grooved branch stripes gradually becomes shallower from the head to the tail, and the depth of the tail of the grooved branch stripes is 0.1-0.3 times the depth of the head of the grooved branch stripes, forming a primary color flow pattern plastic wood board with grooved patterns; (6) weighing nano-silica and γ-(methacryloxy)propyltrimethoxysilane coupling agent in a mass ratio of 100:1-5, adding γ-(methacryloxy)propyltrimethoxysilane coupling agent into water to prepare a coupling agent solution, then adding nano-silica thereto, dispersing evenly, treating for 10-20 minutes, filtering, drying, and dispersing to obtain modified nano-silica; the modified nano-silica has a particle size of 20-100 nm; (7) High-density polyethylene, masterbatch 1, masterbatch 2, antioxidant 1010, nano zinc oxide and stearic acid are weighed respectively according to a mass ratio of 100:1-5:1-5:0.4-0.8:0.4-0.8:0.6-1.2, mixed evenly and added into a granulator, melt blended at 170-190° C., extruded and granulated to obtain aging-resistant colored plastic particles; the particle size of the nano zinc oxide is 20-60 nm; the melt index of the masterbatch 1 and the masterbatch 2 differs by 0.6-6 g / 10 min (2.16 kgf, 190° C.); (8) High-density polyethylene, masterbatch, modified nano-silicon dioxide, graphite powder and stearic acid are weighed respectively according to a mass ratio of 100:1-5:0.6-1.2:0.1-0.3:0.8-1.6, mixed evenly and added into a granulator, melt-blended at 170-190° C., extruded and granulated to obtain wear-resistant colored plastic particles; (9) Adding aging-resistant colored plastic particles and wear-resistant colored plastic particles into two extruders respectively, the processing temperature of extruder one is 160-190° C., and the processing temperature of extruder two is 160-190° C., to form aging-resistant colored plastic molten material flow and wear-resistant colored plastic molten material flow, which are respectively coated on the upper and lower surfaces of the primary colored flow pattern plastic wood board with grooved pattern after being extruded through respective dies to form primary colored flow pattern wood-like board materials, which are then roller extruded, cooled and shaped to obtain colored flow pattern wood-like board materials.
Citation Information
Patent Citations
Co-extruding-molded plastic-wood composite sheet material and preparation method thereof
CN103407262A
Co-extrusion production method for deeply-embossed composite plastic-wood plate with mixed color
CN104004369A
Wood plastic composite material with mixed-color flow lines
CN107139309A
Three-layered coextrusion molding multi-colored plastic-wood composite plate and preparation method thereof
CN109486084A
Preparation method for controlling wood-plastic composite material color mixing flow lines
CN111231356A
